Differential regulation of catecholamine synthesis and transport in rat adrenal medulla by fluoxetine treatment - SPASOJEVIC,NATASA (2015)
We have recently shown that chronic fluoxetine treatment acted significantly increasing plasma norepinephrine and epinephrine concentrations both in control and chronically stressed adult male rats. However, possible effects of fluoxetine on catecholamine synthesis and re-uptake in adrenal medulla have been largely unknown. In the present study the effects of chronic fluoxetine treatment on tyrosine hydroxylase, a rate-limiting enzyme in catecholamine synthesis, as well as a norepinephrine transporter and vesicular monoamine transporter 2 gene expressions in adrenal medulla of animals exposed to chronic unpredictable mild stress (CUMS) for 4 weeks, were investigated. Gene expression analyses were performed using a real-time quantitative reverse transcription-PCR. Chronically stressed animals had increased tyrosine hydroxylase mRNA levels and decreased expression of both transporters. Fluoxetine increased tyrosine hydroxylase and decreased norepinephrine transporter gene expression in both unstressed and CUMS rats. These findings suggest that chronic fluoxetine treatment increased plasma catecholamine levels by affecting opposing changes in catecholamine synthesis and uptake.